2015
DOI: 10.1002/jnr.23602
|View full text |Cite
|
Sign up to set email alerts
|

Association of N‐cadherin levels and downstream effectors of Rho GTPases with dendritic spine loss induced by chronic stress in rat hippocampal neurons

Abstract: Chronic stress promotes cognitive impairment and dendritic spine loss in hippocampal neurons. In this animal model of depression, spine loss probably involves a weakening of the interaction between pre- and postsynaptic cell adhesion molecules, such as N-cadherin, followed by disruption of the cytoskeleton. N-cadherin, in concert with catenin, stabilizes the cytoskeleton through Rho-family GTPases. Via their effector LIM kinase (LIMK), RhoA and ras-related C3 botulinum toxin substrate 1 (RAC) GTPases phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 97 publications
(155 reference statements)
4
59
0
Order By: Relevance
“…The FD Rapid GolgiStain kit (FD Neuro Technologies, Baltimore, MD) was used as recently described (Castaneda et al, 2015). Secondary apical dendrites of pyramidal neurons from the CA1 region were selected for spine analyses (bregma -2.3 to -4.3) (Paxinos and Watson, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…The FD Rapid GolgiStain kit (FD Neuro Technologies, Baltimore, MD) was used as recently described (Castaneda et al, 2015). Secondary apical dendrites of pyramidal neurons from the CA1 region were selected for spine analyses (bregma -2.3 to -4.3) (Paxinos and Watson, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study has shown that EA at Baihui (DU20) and Shenting (DU24) acupoints could improve cognitive impairment through Rho GTPases to enhance dendritic plasticity in rats with ischemic stroke [27]. Interestingly, it has been suggested that the activation of the Rho GTPases signaling is essential for LIMK1 activation by phosphorylation on threonine 508, which is widely known as master regulator of actin dynamics [28, 29]. Thus, the study aimed to elucidate whether EA at the DU20 and DU24 acupoints could improve the cognitive deficits in rats with ischemic stroke via miRNA-LIMK1-mediated synaptic plasticity to enhance spatial reference learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…For example, social defeat induces both neuroendocrine and behavioral modifications (Keeney et al., 2001), as well as neurobiological alterations across several brain regions that are particularly vulnerable to stress, including the hippocampus (Tse et al., 2014). More specifically, it is reported that the CA1 subregion of the hippocampus displays morphological changes as a consequence of stress exposure (Castaneda et al., 2015, Sebastian et al., 2013a); however, this relationship has yet to be examined during the juvenile stage of development, as a function of social stress specifically. Thus, in order to characterize the effects of social stress on hippocampal spine morphology during adolescence, we examined the expression of synaptic markers within CA1 spines.…”
Section: Introductionmentioning
confidence: 99%